Use of the 1H NMR technique to describe the kneading step of wholewheat dough: The effect of kneading time and total water content. (15th February 2021) - Parenti, Ottavia; Guerrini, Lorenzo; Zanoni, Bruno; Marchini, Mia; Tuccio, Maria Grazia; Carini, Eleonora
Highlights: The 1 H NMR technique monitored the kneading step of a wholewheat flour (WWF) dough. The effect of the kneading time and the total water content was investigated. The 1 H NMR signals were interpreted as biopolymer physical/chemical transformations. Different water contents changed the proton mobility and dynamics of WWF doughs. The 1 H NMR technique is able to monitor dough molecular evolution during kneading. Abstract: The kneading step of wholewheat flour (WWF) dough was monitored using low-resolution 1 H nuclear magnetic resonance (NMR). The tested variables were kneading time and total water content. Two 1 H Free induction decay (FID) (A and B) and four 1 H T2 Car-Purcell-Meiboom-Gill (CPMG) (C, D, E and F) proton populations were observed and the attribution to the different proton domains was made based on the literature and data acquisition. Kneading time significantly increased the mobility and the relative abundance of popA, the relative abundance and strength of protons of popC, D and E, while significantly reducing the relative amount of popF and increasing its mobility. This evolution of the proton populations during kneading was interpreted as chemical/physical transformations of the flour constituents. The use of WWF may reveal the changes in molecular dynamics underlying the higher water requirements of unrefined doughs, often associated with improved bread quality.